Border Settlement Dynamics and Border Status Quo: A Comparative Analysis of Turkey's Borders - Oztig, Lacin Idil; Okur, Mehmet Akif (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
There is a plethora of research on border disputes, border dispute resolution, unsettled borders, and artificially drawn borders. Yet, no study has so far been conducted on the comparative analysis of borders settled with mandatory powers and between nation-states. This article fills this research lacuna and makes a novel contribution to border scholarship by exploring the linkages between border settlement dynamics and the border status quo. In analysing and comparing Turkey's borders drawn between the 1920s and the 1930s, it is shown that Turkey's Iraqi and Syrian borders settled with mandatory powers (Britain and France respectively) have resulted in the emergence of alternative border imaginations by one of the neighbouring states, albeit without reaching the level of an official demand to change the status quo. Since its independence, Syria has produced an alternative border imagination with respect to its Turkish border by showing Turkey's Hatay province within its borders in its official maps and documents. Since the cession of Mosul to Iraq, Turkey's alternative border imagination has taken the form of state actors' contemplations about resettling the border. In sharp contrast, the Turkish-Iranian border, settled after long consultations between two independent nation-states, effectively resolved boundary-related problems, resulting in the mutual endorsement of the border status-quo. This article concludes that border settlement processes create path-dependent effects that are carried over to subsequent generations of state actors.
Keywords: INTERNATIONAL BORDERS; MOSUL DISPUTE; CONTROVERSY; TERRITORY; FRONTIER; TREATY; WORLD; Geography; Government & Law